'Dr. Google, I have a stomach ache' – seasonal variations in abdominal pain: a 4-year retrospective data analysis from Google Ads keywords planner. (July 2020) - Kamiński, Mikołaj; Łoniewski, Igor; Marlicz, Wojciech
Background: Internet traffic may reflect the prevalence of real-world ailments. The aim of this study was to analyse queries associated with abdominal pain and to investigate seasonal frequency and trends of searches in Poland. Methods: We analysed mean search volume from March 2015 to February 2019 of keywords associated with 'abdominal pain' in the Polish language generated from the Google Ads Planner. Keywords were categorised by location, feature or type of pain, concurrent symptoms, frequency and patient groups, etc. We compared differences in search volumes across seasons and years. Results: Overall, 24, 673, 430 queries were associated with abdominal pain in the period analysed. The number of searches associated with abdominal pain in winter increased by 30% compared with queries searched in summer. There were significantly more searches related to abdominal pain located in the epigastric, umbilical, hypogastrium, left lumbar, left iliac and right iliac regions combined with vomiting or fever, and acute or burning sensation in cold months. We did not observe any specific patterns of pain in the right lumbar or left hypochondrium region, co-presence of flatulence, acute, cramping or persistent/chronic or strong abdominal pain. Conclusion: Internet queries associated with abdominal pain and related factors have increased in the past 4 years and present a seasonal pattern. Google Ads may be a valuable tool to assess the prevalence of complaints in under-researched regions. The observed trends in queries related to abdominal pain merely reflect the scale of the problem. The reported pattern should be verified in epidemiological studies.